Method for Measuring Speech Enhancement of Electronic Hearing Protection Device: A Systematic Review - Mohamad Zaki, Siti Syahzanan; Razali , Ailin; Abdul Qahar, Muhammad Mawaddi (IIUM Medical Journal Malaysia, 2025)
The usage of electronic hearing protection devices (e-HPDs) among industrial workers has been introduced among others, to allow more effective communication in noisy environments. The effectiveness of the speech enhancement element of e-HPDs thus needs to be assessed. To date, no standardized speech enhancement assessment method is available. This systematic review aimed to compile and synthesize available information in the literature on speech perception test method of e-HPDs while also assessing the quality of selected studies. The Cochrane methodology was used, with the findings documented using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and checklist. The International Prospective Register of Systematic Reviews (PROSPERO) was utilized to register this systematic review, with the CRD number assigned as CRD42024526086. Five electronic databases were explored: PubMed, ProQuest, IEEE, Scopus, and ScienceDirect. The quality appraisal was conducted based on Effective Public Health Practice Project (EPHPP) tool. In total ten studies were reviewed, utilizing several speech tests including Hearing in Noise Test (HINT), Speech Recognition in Noise Test (SPRINT), Callsign Acquisition Test (CAT), Modified Rhyme Test (MRT), Quick Speech in Noise Test (QuickSIN), Dutch Monosyllabic Speech Test and Mandarin Disyllabic Word Discrimination Test (WDT) to evaluate speech enhancement capabilities in e-HPDs. In conclusion, speech tests are essential for assessing how well e-HPDs perform enhancing speech in noisy environments. HINT has the strongest quality compared to other speech test for e-HPDs assessment. HINT or its modifications can subsequently be considered in the anticipated standardized speech perception test method of e-HPDs tests worldwide